On the Christian Anthropological Foundations of Modern Western Rule of Law - SHI Liang, (Journal of Research for Christianity in China (JRCC), 2025)
Different types of presuppositions about human nature lead to rationalizations for different types of legal orders, providing cultural and ideological support from deep cultural resources for the practical operation of such legal systems. This paper argues that the anthropological foundation laid by the Christian tradition for Western rule of law is not the commonly assumed Western doctrine of innate evil, but rather a composite anthropology of “sinful human nature.” This anthropology ultimately directs the logic of order construction toward respecting human intrinsic value while guarding against human depravity, and upholding the independent status of law. This constitutes the anthropological premise for the rule of law logic in modern Western civilization—a logic that prevents evil and promotes good through the enactment, implementation, and reform of laws.